1977
DOI: 10.1021/i260064a008
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Calcination and Recarbonation of Calcined Dolomite

Abstract: Results on the cyclic calcination and recarbonation of calcined dolomite at atmospheric pressure and at 300 psig are presented. The effects of various reaction parameters (i.e., temperature, pressure, and gas composition) on the recarbonation rate and on the change in solid reactivity with cycling were explored. Addition of steam to the recarbonation atmosphere resulted in nearly a two order of magnitude increase in the recarbonation rate. Increasing the temperature and the partial pressure of carbon dioxide f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 16 publications
7
63
0
Order By: Relevance
“…These properties depend on impurities and the conditions / age of formation. Dolomites have shown a reduced decay rate upon cycling, despite a lower initial reactivity owing to a lower amount of CaO per unit mass (Dobner et al, 1977;Silaban et al, 1996); natural sorbents such as shells have also been studied and have been shown to exhibit mildly increased reactivity in comparison to natural limestone in some cases (Ives et al, 2008;Li et al, 2009). Doping of natural limestones has been investigated; however the results have been variable (Salvador et al, 2003;Fennell et al, 2007b;Florin and Harris, 2008b;Sun et al, 2008), even when the same dopant has been used.…”
Section: Sorbent Performancementioning
confidence: 99%
“…These properties depend on impurities and the conditions / age of formation. Dolomites have shown a reduced decay rate upon cycling, despite a lower initial reactivity owing to a lower amount of CaO per unit mass (Dobner et al, 1977;Silaban et al, 1996); natural sorbents such as shells have also been studied and have been shown to exhibit mildly increased reactivity in comparison to natural limestone in some cases (Ives et al, 2008;Li et al, 2009). Doping of natural limestones has been investigated; however the results have been variable (Salvador et al, 2003;Fennell et al, 2007b;Florin and Harris, 2008b;Sun et al, 2008), even when the same dopant has been used.…”
Section: Sorbent Performancementioning
confidence: 99%
“…The surface area of the catalyst was measured by the BET method with a Quantachrome MgO remains chemically inert [28,29]. Other compounds are finely dispersed in small crystallites on dolomite [30]. Earlier studies [31] showed that using a mixture of reforming catalyst and CaO (derived from calcinations of high-purity CaCO 3 ) in a single reactor, high H 2 concentration of >95% could be achieved.…”
Section: Solids Characterisationmentioning
confidence: 99%
“…For example, Qin et al [17] studied various heat pre-treatment procedures with CaO/CuO pellet mixing to overcome the loss of performance and found that certain thermal treatments improved the multi-cycle CaL stability. Steam, which is present in post combustion flue gas, has also been demonstrated to have a positive effect on the stability of pure CaO pellets to capture CO 2 over multiple cycles [17][18][19][20][21][22][23][24]. Several theories have been proposed to explain how steam improves the CaL process.…”
Section: Introductionmentioning
confidence: 99%